Attitudes in music practice: a survey exploring the self-regulated learning processes of advanced Brazilian and Portuguese musicians - dos Santos Silva, Camilla; Araújo, Marcos Vinícius; Marinho, Helena (Frontiers in Psychology, 2024)
This descriptive study aimed to investigate the Self-Regulated Learning behaviors of advanced Brazilian and Portuguese musicians and how these processes vary in terms of gender, nationality, musical instrument, quantity of practice, expertise, and professional experience. 300 participants fully completed the 22-item questionnaire “Attitudes in music practice” designed by Araújo (2016). The sample comprised of 54.3% males, 44.0% females, and 1% non-binary; 0.7% did not respond. 68.0% (n = 204) were Brazilian, and 32.0% (n = 96) were Portuguese. The mean age was 32.70 years old (SD = 11.261), the mode was 22 years old, with a range of 18 to 66 years. Similar to the first study by Araújo (2016), Exploratory Factor Analysis generated three factors: Practice Organization, Personal Resources, and External Resources. The results report there are no differences in SRL scores in terms of gender, nationality, and musical instrument. However, One-way ANOVA test results convey differences in SRL scores and the quantity of practice and expertise with those musicians who reported practicing for longer periods scoring more highly than participants who declared spending less time on daily practice. The results for the expertise variables suggest that more experienced and older musicians scored higher in “Personal Resources” and lower in “External Resources” indicating that, as musicians gain in experience, their metacognitive processes become more evident than the social factors of their performance.